2023
DOI: 10.1136/bmjresp-2023-001667
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study evaluating the impact of SARS-CoV-2 variants on Long COVID outcomes in UK hospital survivors

Abstract: ObjectivesCOVID-19 studies report on hospital admission outcomes across SARS-CoV-2 waves of infection but knowledge of the impact of SARS-CoV-2 variants on the development of Long COVID in hospital survivors is limited. We sought to investigate Long COVID outcomes, aiming to compare outcomes in adult hospitalised survivors with known variants of concern during our first and second UK COVID-19 waves, prior to widespread vaccination.DesignProspective observational cross-sectional study.SettingSecondary care tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This study found that, compared to those who had no reported history of COVID-19 infection, or had recovered, those with long COVID had more severe symptoms of depression, anxiety, and psychological distress and reported more days out of role, indicating the functional impact of the symptoms. This is unsurprising given that a range of chronic conditions are known to be associated with poorer mental health outcomes, including those that also have the potential to increase people’s susceptibility to a severe COVID-19 infection, such as cardiovascular disease [ 25 , 26 , 27 ]. Also consistent with previous research, the patients reported cognitive difficulties, such as memory loss, confusion, and difficulty concentrating [ 28 ], and future research is planned to look at how digital mental health services can address the cognitive and mental health impacts of COVID-19 in both the short term and long term.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that, compared to those who had no reported history of COVID-19 infection, or had recovered, those with long COVID had more severe symptoms of depression, anxiety, and psychological distress and reported more days out of role, indicating the functional impact of the symptoms. This is unsurprising given that a range of chronic conditions are known to be associated with poorer mental health outcomes, including those that also have the potential to increase people’s susceptibility to a severe COVID-19 infection, such as cardiovascular disease [ 25 , 26 , 27 ]. Also consistent with previous research, the patients reported cognitive difficulties, such as memory loss, confusion, and difficulty concentrating [ 28 ], and future research is planned to look at how digital mental health services can address the cognitive and mental health impacts of COVID-19 in both the short term and long term.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies representing a range of global regions have investigated the likelihood of developing long-term sequelae following COVID-19 infection according to variant of infection, with studies consistently finding a lower likelihood of long-term sequelae following infections with the Omicron variant compared to the ancestral Wild Type strain or subsequent variants of concern (VoCs) (920). There is some evidence that Wild Type infections were associated with a greater likelihood of developing long-term sequelae compared to subsequent variants (9,12,16,21), though between-variant differences prior to Omicron are less consistent across studies. However, current understanding of the impact of SARS-CoV-2 variant on likelihood of post-acute sequelae are impacted by several methodological concerns.…”
Section: Introductionmentioning
confidence: 99%